PERCEPTIONS OF ALGORITHMIC PROFILING ON FACEBOOK AND THEIR SOCIAL IMPLICATIONS - Tamò Larrieux, Aurelia; Fosch Villaronga, Eduard; Velidi, Shruthi; Viljoen, Salome; Lutz, Christoph; Büchi, Moritz (AoIR Selected Papers of Internet Research, 2020)
With every digital interaction, individuals are increasingly subject to algorithmic profiling, understood as the systematic and purposeful recording and classification of data related to individuals. Large Internet firms, such as Facebook and Google/Alphabet, as well as third-party data brokers collect and combine detailed personal data to create sophisticated profiles for predictive purposes. Research has started to look into people’s perception and engagement of algorithms, showing that many users are unaware of the existence of algorithms, for example those which curate news feeds, and that a majority feels uncomfortable with algorithmic profiling on Facebook. In our research, we investigate perceptions of algorithmic profiling on Facebook by addressing the following questions: What user narratives of profiling on Facebook exist? What reactions do users have when confronted with Facebook’s inferred profiles? What are the social implications of user perceptions of profiling? Drawing on rich and recent survey data from 292 US-based Facebook users, we identified four overarching themes relating to Facebook’s profiling activities: uncertainty, naiveté, realism, and fatalism. While the third theme is the most prevalent, Facebook is perceived as very powerful when it comes to algorithmic profiling. However, when confronted with their own profiles through the "My interests" and "My categories" sections in the Facebook Ad preferences menu, many users indicated surprise at how imprecise or even wrong some of the inferred interests and categories were. We discuss the social implications of our findings with regards social exclusion and social justice.